2016
DOI: 10.17576/mjas-2016-2002-26
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Analyses of Malaysian Stingless Bee Propolis Extracts

Abstract: The aim of this study is to evaluate chemical and biological profile of methanol extracts from Malaysian propolis produced by two commonly found stingless bee species, Heterotrigona itama (MHI) and Geniotrigona thoracica (MGT). Test samples were analyzed for physicochemical parameters such as moisture, fat, crude fibre, crude protein, carbohydrate and ash content. Tests for phytochemical screening by thin layer chromatography of both extracts revealed that presence of terpenoids, flavonoids, phenols and essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 17 publications
3
35
1
1
Order By: Relevance
“…Therefore, ABTS + radical scavenging assay was selected to analyse the antioxidant activity of EEP since ABTS + has a rapid kinetic reaction and intense response to antioxidants [ 42 ]. As suggested by Ibrahim et al [ 5 ], the increment of antioxidant activity can be observed in the increase of radical scavenging activity that corresponded to a lesser value of IC 50 of the extract. This is in agreement with our present study, where the EEP of T. apicalis possess inhibitory activity against ABTS + radical with IC 50 of 1.68 mg/mL although positive control (Trolox) was better with IC 50 of 0.31 mg/mL.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, ABTS + radical scavenging assay was selected to analyse the antioxidant activity of EEP since ABTS + has a rapid kinetic reaction and intense response to antioxidants [ 42 ]. As suggested by Ibrahim et al [ 5 ], the increment of antioxidant activity can be observed in the increase of radical scavenging activity that corresponded to a lesser value of IC 50 of the extract. This is in agreement with our present study, where the EEP of T. apicalis possess inhibitory activity against ABTS + radical with IC 50 of 1.68 mg/mL although positive control (Trolox) was better with IC 50 of 0.31 mg/mL.…”
Section: Discussionmentioning
confidence: 61%
“…In Malaysia, multiple researches have been conducted to observe the effectiveness of propolis for some biological activities. The detection of phytochemical compounds and antioxidant activity of Malaysian propolis was successfully discussed in several studies using gas chromatography-mass spectrometry (GC-MS) and thin-layer chromatography (TLC) [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, research on propolis is limited and until now there are only a few preliminary investigations on the composition and biological activity of propolis derived from Malaysian stingless bees [18]. This study was aimed in analyzing the phytochemical profile of T. apicalis propolis and its antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse biological properties and wide application of geopropolis in modern medicine have meant increasing attention has been paid to the identification of new sources of geopropolis and to the study of their chemical composition. Recently, a form of geopropolis produced by stingless bees ( Heterotrigona itama ) and collected in the state of Sarawak, Malaysia, has been shown to exhibit antibacterial activity as well as antioxidant, nitric oxide scavenging, and antidiabetic activities [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical constituents of this geopropolis have been tentatively studied based on thin layer chromatography and color reactions [ 11 , 12 ]. The results showed that its methanol extract was composed of terpenoids, flavonoids, phenols, steroids, saponin, and coumarins.…”
Section: Introductionmentioning
confidence: 99%